Using technology to enhance motivation in teaching English to young learners in Uzbekistan - Sabrina Ilkhomova; Mukhabat Ikromovna Tursunova (Science and Education, 2026)
In modern education, technology plays an increasingly important role in improving the quality of teaching and learning. In Uzbekistan, the integration of technology into English language education has become one of the key priorities of educational reform. This article examines how technology can enhance motivation among young learners studying English as a foreign language. The study focuses on the use of multimedia tools, educational applications, and interactive digital resources in primary school classrooms. The research is based on classroom observations, questionnaires, and interviews with students. The findings show that the use of technology increases students’ interest, participation, and confidence. Students are more motivated when lessons include videos, games, and interactive exercises. The article concludes that technology is an effective motivational tool that can improve learning outcomes and support innovative teaching practices in Uzbekistan.